Mechanisms of σ54-Dependent Transcription Initiation and Regulation. Issue 20 (20th September 2019) - Danson, Amy E.; Jovanovic, Milija; Buck, Martin; Zhang, Xiaodong
Abstract: Cellular RNA polymerase is a multi-subunit macromolecular assembly responsible for gene transcription, a highly regulated process conserved from bacteria to humans. In bacteria, sigma factors are employed to mediate gene-specific expression in response to a variety of environmental conditions. The major variant σ factor, σ 54, has a specific role in stress responses. Unlike σ 70 -dependent transcription, which often can spontaneously proceed to initiation, σ 54 -dependent transcription requires an additional ATPase protein for activation. As a result, structures of a number of distinct functional states during the dynamic process of transcription initiation have been captured using the σ 54 system with both x-ray crystallography and cryo electron microscopy, furthering our understanding of σ 54 -dependent transcription initiation and DNA opening. Comparisons with σ 70 and eukaryotic polymerases reveal unique and common features during transcription initiation. Graphical Abstract: Unlabelled Image Highlights: Mechanism of transcription inhibition by σ 54 Coupled load and unwind model for transcription initiation Role of bacterial enhancer-binding proteins in isomerization to the open complex Comparison of structural and functional differences between σ 70 and σ 54